2012
DOI: 10.1021/es3000905
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms and Humans in Vitro: Characterizing Evolutionarily Conserved Stress and Immune Responses to Silver Nanoparticles

Abstract: Little is known about the potential threats of silver nanoparticles (AgNPs) to ecosystem health, with no detailed report existing on the stress and immune responses of soil invertebrates. Here we use earthworm primary cells, cross-referencing to human cell cultures with a particular emphasis on the conserved biological processes, and provide the first in vitro analysis of molecular and cellular toxicity mechanisms in the earthworm Eisenia fetida exposed to AgNPs (83 ± 22 nm). While we observed a clear differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 39 publications
9
94
2
2
Order By: Relevance
“…Briefly, coelomocytes were extruded from earthworms using a physiological saline containing 2% ethanol, guaicolglyceryl-ether (a mucolytic agent) and EDTA. In accordance with the previous study, we conducted in vitro assays under isotonic conditions using an osmolarity-adjusted phosphate-buffered saline (PBS) or cell culture medium to achieve osmolarity equivalent to Lumbricus balanced salt solution (176 mOsm; for the composition see Hayashi et al, 2012). Thus, we refer to the osmolarityadjusted PBS as reduced PBS or ''R-PBS''.…”
Section: Cell Harvesting and Exposure Conditionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Briefly, coelomocytes were extruded from earthworms using a physiological saline containing 2% ethanol, guaicolglyceryl-ether (a mucolytic agent) and EDTA. In accordance with the previous study, we conducted in vitro assays under isotonic conditions using an osmolarity-adjusted phosphate-buffered saline (PBS) or cell culture medium to achieve osmolarity equivalent to Lumbricus balanced salt solution (176 mOsm; for the composition see Hayashi et al, 2012). Thus, we refer to the osmolarityadjusted PBS as reduced PBS or ''R-PBS''.…”
Section: Cell Harvesting and Exposure Conditionsmentioning
confidence: 97%
“…Soluble silver fraction (dissolved silver complexes and free Ag + ) of NM-300K under the exposure condition (2 mg/ml, 4 h and 24 h in CCM) was determined using an ultracentrifugation method (for details see Beer et al, 2012;Foldbjerg et al, 2012;Hayashi et al, 2012). Briefly, following incubation in quadruplicate, NM-300K was ultracentrifuged at 50 000 rpm (corresponding to 70 000-135 000 Â g) for 30 min at 4 C and the supernatant was digested in 69% HNO 3 (tracemetal grade, Sigma-Aldrich).…”
Section: Quantification Of Dissolved Silver and Cellular Silver Burdensmentioning
confidence: 99%
“…Additionally, Ag nanoparticles induce a reduction of NO production and an upregulation of the expression of Myd88, MEKK1 and early regulation of oxidative stress genes, in both PBMCs and THP-1 cells. (Hayashi et al, 2012) Similarly, exposure for 24, 48 or 72 h to 1e25 ppm Ag nanoparticles causes a significant decrease in the cell viability of murine peritoneal macrophages, and exposure to 0.4e25 ppm of Ag nanoparticles results in a significant decline in NO production by murine macrophages (Shavandi et al, 2011). The in vitro exposure of murine macrophages to 50e100 mg/mL Ag nanoparticles results in a significant reduction in cell viability, with an investigation of intracellular localization revealing silver distributed mainly to high molecular weight proteins, and Ag nanoparticles co-localizing with lysosomes.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Nguyen et al (2012) found that mouse macrophage cells (J774A.1) were more sensitive to CdTe-QD exposure than human colonic epithelial cells (HT29), in terms of metabolism loss, changes in morphology and rate of QD internalization. Differences in sensitivity and uptake of nanoparticles were also found between coelomocytes and a cultured cell line, in a study by Hayashi et al (2012). This study demonstrated that coelomocytes from the earthworm Eisenia fetida were more sensitive to silver nanoparticle exposure than the cultured human leukaemia (THP-1) cell line and also accumulated more silver nanoparticles.…”
Section: Discussionmentioning
confidence: 60%